(untitled) (Conferencea, 2023)
This article is devoted to The problem of further improving the constitutional framework for the activities of political parties: the example of Uzbekistan and Tajikistan. In the article, The constitutional content of the activities of political parties has been studied based on comparison between countries’ experience and its specific features have been revealed.